2012
DOI: 10.2136/sssaj2011.0128
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Organic Matter Pools and Increases in Carbon Sequestration in Response to Surface Liming in an Oxisol under Long‐Term No‐Till

Abstract: In a no-till system (NTS) on naturally acidic soils, surface liming is essential to neutralize soil acidity and increases crop productivity. As a result, the soil organic matter (SOM) pools of the soil surface layers may change, reflecting increased C inputs by crop residues. The objective of this study was to quantify changes in SOM pools and the rate of C sequestration that occur in response to surface liming in a long-term NTS experiment. The experiment was conducted in an Oxisol in southern Brazil. The tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 46 publications
(62 reference statements)
2
32
0
4
Order By: Relevance
“…The soil organic matter (SOM) fractions are more sensitive for revealing changes caused in the soil coming from the different management systems compared to the total organic carbon (TOC) (Briedis et al, 2012). Some studies showed that the decomposition of organic matter was reduced in flooded soil, such as in submerged rice paddy soils (Bell, 1969).…”
Section: Introductionmentioning
confidence: 99%
“…The soil organic matter (SOM) fractions are more sensitive for revealing changes caused in the soil coming from the different management systems compared to the total organic carbon (TOC) (Briedis et al, 2012). Some studies showed that the decomposition of organic matter was reduced in flooded soil, such as in submerged rice paddy soils (Bell, 1969).…”
Section: Introductionmentioning
confidence: 99%
“…These results indicate that the action of the calcium carbonate in micron particles occurred only near the application area. Furthermore, the low amount of liming material applied (12.6 kg ha -1 at the maximum rate used) was not enough to cause significant changes in these nutrients, which usually ranges from 1 to 22 Mg ha -1 (Miranda et al, 2005;Caires et al, 2008;Briedis et al, 2012;Pagani and Mallarino, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…As a suggestion for new research application of conventional lime to the surface and liquid lime in the sowing furrow until the conventional lime has a chance to increase pH is a potential area of study. Thus, this combination with traditional liming and liquid liming can provide more promising results than simply applying liming on the soil surface, which, in NTS, takes even longer to react with the soil (Caires et al, 2008;Briedis et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Além disso, a aplicação de calcário líquido, aliada à calagem tradicional, pode proporcionar resultados mais promissores do que somente a calagem tradicional. Esta, no sistema plantio direto, demora ainda mais a reagir com o solo (Caires et al, 2008;Briedis et al, 2012).…”
Section: Experimento 1 (Doses De Caco 3 )unclassified